Rigorous ESR spectroscopy of Fe3+ impurity ion with oxygen vacancy in ferroelectric SrTiO3 crystal at 20 mK. (28th June 2018) - Hosain, M A; Le Floch, J-M; Krupka, J; Tobar, M E
Abstract: Impurity Fe 3+ ion electron spin resonance (ESR) spectroscopy using multiple dielectric modes in a SrTiO3 dielectric resonator has been performed with a tunable DC magnetic field of up to 1.6 T. The Ti ion is substituted by Fe 3+ ion forming FeO6 octahedral complex with an iron-oxygen-vacancy (Fe ). In such a metal-ligand complex, a giant g -factor of was observed in the ferroelectric phase at 20 mK. The change of Fe 3+ ion center-symmetry in the FeO6 complex as a soft-mode characteristics of ferroelectric phase transition and the influences of iron-oxygen-vacancy (Fe ), are interactively sensitive to asymmetry in the octahedral rotational parameter Φ in SrTiO3 .